Synthesis of New Schiff Bases and 2,3-Disubstituted 1,3-Thiazolidin-4-one Derivatives Containing Benzothiazole Moiety - Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two series of Schiff Bases and 2,3-disubstituted-1,3-thiazolidin-4-one derivatives were synthesized . Reaction of 2-mercaptobenzothiazole with Î±-chloro acetic acid gave compound[I]. Esterification of carboxylic moity of compound [I] , using absolute methanol in the presence of conc . H2SO4 yielded acorresebonding ester [II] , wich was condensation with hydrazine hydrate to give acid hydrazide [III] . The new Schiff bases [V]n were synthesized by reaction of acid hydrizide with dialdehyde [IV]n in the presence of glacial acetic acid . The thiazolidinone derivatives [VI]n have been obtained from the azomethines through the addition of thioglycolic acid . Their chemical structures have been confirmed by melting points , FTIR and 1HNMR (of some of them) . Benzothiazole , thiazolidinone.